Experimental evaluation on natural composites with the incorporation of metal powders. (2020) - Kumar, T. Raj; Vijayan, V.; Yokeswaran, R.; Saravanan, K.; Ragulnath, D.; ArunKumar, G.; Parameswaran, P.
Abstract: The study is based on the investigation of mechanical properties in hybrid FRP which is fabricated with epoxy polymer, natural and glass fibres, and addition of silicon and copper powder. The natural fibres of chopped banana fibres were also reinforced for increasing the strength of composites. The E-glass fibre were added and analysed its properties. The result showed that, the mechanical properties were improved due to the silicon and copper metal powder additions. The water absorption test was also taken and found the improvement in the hybrid composites due to the added metal powders.